Displacement mechanical amplifiers designed on poly-silicon - Ramon Cabello-Ruiz; Margarita Tecpoyotl-Torres; Alfonso Torres-Jacome; Gerardo Vera-Dimas; Svetlana Koshevaya; Pedro Vargas-Chable (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Using Poly-Silicon, the implementation of novel Displacement-amplifying Compliant Mechanisms (DaCM), in two geometries of accelerometers, allows for remarkable improvements in their operation frequency and displacement sensitivity, with different proportions. Similar DaCM´s geometries were previously implemented by us with Silicon. In all mentioned cases, the geometries of DaCM´s are adjusted in order to use them with Conventional Capacitive Accelerometer (CCA) and Capacitive Accelerometer with Extended Beams (CAEB), which operate in-plane mode, (y-axis). It should be noted that CAEB shows improvements (95.33%) in displacement sensitivity compared to ACC. Simulations results, carried out using Ansys Workbench software, validate the system’s performance designed with Poly-Silicon. Finally, a comparison with the similar systems, previously designed with Silicon, is also carried out.